Advances in the design of symbolic computation systems - Miola, A. (Alfonso) 1944-; Temperini, M. (Marco) (Texts and monographs in symbolic computation, 1997)
Considers methodological aspects related to design and implementation of symbolic computation systems. This volume describes the proposed treatment of mathematical objects, via techniques for method abstraction, structures classification, and exact representation, the programming methodology which supports the design and implementation issues.